Prevalence of Upper Extremity Musculoskeletal Disorders in Dentists: Symptoms and Risk Factors - Rafie, Forouzan (J Environ Public Health, 2015)
Aim. The purpose of the present research was to examine the factors that lead to musculoskeletal disorders in dentists by assessing their posture using RULA method. Materials and Methods. In this cross-sectional study, 130 dentists (84 male and 46 female) participated. The posture of the subjects during their normal workload was recorded by using the RULA method, and the range of musculoskeletal pains by using the Nordic Musculoskeletal Questionnaire (NMQ), and individual and professional data was assessed by a demographics questionnaire. All tests were performed at the P < 0.05 level. Results. Assessment of the physical status of the subjects showed that 82.8% of subjects were at high risk of musculoskeletal disorders. The majority of musculoskeletal pains were in the neck (55.9%) and the shoulder (43.8%). Moreover, 68.9% of the subjects had experienced pain at least once over the last year. Significant relationships were observed between musculoskeletal pain and daily work hours (P = 0.07) and number of patients (P = 0.02), but the pain was not significantly associated with BMI and experience. Conclusion. The present findings showed that unsuitable posture of dentists during work has a considerable effect on musculoskeletal disorders. Therefore, further investigation is required to avoid the detrimental effects of wrong posture.